2020
DOI: 10.1093/ofid/ofaa439.765
|View full text |Cite
|
Sign up to set email alerts
|

571. “Real world” Impact of Letermovir for Prevention of Cytomegalovirus Infection in Hematopoietic-Cell Transplantation

Abstract: Background Letermovir (LTM) was FDA-approved in 2017 for cytomegalovirus (CMV) prophylaxis in allogeneic hematopoietic cell transplant (HCT) patients. We evaluated the “real-world” impact of LTM in adult HCT recipients at the Mount Sinai Hospital in New York following addition of LTM to our formulary in June 2018. Methods In this retrospective study, we compared 31 consecutive allogeneic HCT recipients from June 2018-June 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…At D+100, time to CMVr in the letermovir group ranged from a median of 10 days (interquartile range [IQR], 5–38 days) [ 24 ] to 38 days (IQR was not reported in these 2 studies) [ 25 , 26 ]. At D+200, time to any detectable CMV viremia ranged from a median of 19 days (IQR, 14–67 days) [ 27 ] to 67 days (IQR, 32–100 days) [ 28 ]. At D+100, duration of CMVr was lower in the letermovir group compared to the control group in several studies that reported the data and ranged from a median of 3 days (IQR, 1–24 days) [ 29 ] to 29 days (IQR, 26–38 days) [ 30 ] in the letermovir group compared to a range of 27 days (IQR, 3–99 days) [ 29 ] to 42 days (IQR, 31–54 days) in the control group [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…At D+100, time to CMVr in the letermovir group ranged from a median of 10 days (interquartile range [IQR], 5–38 days) [ 24 ] to 38 days (IQR was not reported in these 2 studies) [ 25 , 26 ]. At D+200, time to any detectable CMV viremia ranged from a median of 19 days (IQR, 14–67 days) [ 27 ] to 67 days (IQR, 32–100 days) [ 28 ]. At D+100, duration of CMVr was lower in the letermovir group compared to the control group in several studies that reported the data and ranged from a median of 3 days (IQR, 1–24 days) [ 29 ] to 29 days (IQR, 26–38 days) [ 30 ] in the letermovir group compared to a range of 27 days (IQR, 3–99 days) [ 29 ] to 42 days (IQR, 31–54 days) in the control group [ 30 ].…”
Section: Resultsmentioning
confidence: 99%